Effects of Exercise Training on Growth and Differentiation Factor 11 Expression in Aged Mice - Lee, Minjung; Oikawa, Satoshi; Ushida, Takashi; Suzuki, Katsuhiko; Akimoto, Takayuki (Frontiers in Physiology, 2019)
Exercise training is considered an effective way to prevent age-related skeletal muscle loss. However, the molecular mechanism has not been clarified. Growth and differentiation factor 11 (GDF11) has been controversially considered a regulator of skeletal muscle aging. In this study, we examined whether GDF11 is associated with skeletal muscle aging and the effects of exercise training on age-related skeletal muscle loss. First, we observed that Gdf11 mRNA and protein expression levels in young (5-month-old, n = 6) and aged (22–26-month-old, n = 5) mice were not significantly different. Aged mice were then divided into sedentary (n = 5) and exercise (n = 6) groups. The exercise group performed moderate-intensity treadmill running for 6 weeks. Treadmill exercise training increased Gdf11 mRNA expression in the soleus muscle, but its protein expression was not altered. In contrast, the GDF11 level in the plantaris muscle was not changed at either the mRNA or protein level. Collectively, our data demonstrate that GDF11 levels do not change during aging, and that treadmill exercise training increased Gdf11 mRNA expression in a predominantly slow-twitch muscle.